ANALISIS KEPATUHAN PAJAK FINANSIAL DAN NON FINANSIAL SERTA KOREKSI FISKAL - Agus Widodo (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2016)
This research aims to analyze the financial tax compliance PT XYZ in calculating, amount of pavment, and amount of reporting tax obligations (Value Added Tax (VAT), Article 21 Income Tax, Articic 23 Income Tax, Article 4 (2) Income Tax, Article 25 Income Tax, Corporate Income Tax) and the non financial tax compliance PT XYZ related to the date of tax payment and tax reporting (Value Added Tax (VAT), Article 21 Income Tax, Article 23 Income Tax, Article 4 (2) Income Tax, Article 25 Income Tax, Corporate Income Tax) before due of tax payment and tax reporting also fiscal correction has been done in 2014 in accordance with applicable tax laws in 2014.